Effect of a Buttiauxella phytase on production performance in growing/finishing pigs fed a European-type diet without inclusion of inorganic phosphorus. (7th March 2017) - Dersjant-Li, Yueming; Schuh, Katharina; Wealleans, Alexandra L.; Awati, Ajay; Dusel, Georg
Summary: The effect of a Buttiauxella phytase, in a dose range of 0-1000 FTU/kg in feed, on production performance in growing/finishing pigs fed European type wheat, corn, barley and SBM based diet was determined. Five dietary treatments were tested including a positive control (PC), a negative control (NC) without inorganic P and with reduced Ca (–0.12%) and metabolisable energy content (–0.14 MJ ME/kg) or NC supplemented with Buttiauxella phytase (Axtra ® PHY, Danisco Animal Nutrition, DuPont Industrial Biosciences, Marlborough, UK) at 250, 500 or 1000 FTU/kg respectively. A total of 100 pigs (mean initial BW of 30 kg, Topig x Pi, 10 weeks of age) were used, with 20 replicates per treatment (50% gilts and 50% barrows). Pigs were individually housed in pens and randomly allocated on the basis of body weight (BW) and gender to the five treatments. Feed, in mash form, and water were offered ad libitum . Basal diets had an intrinsic phytase level of approximately 300 and 440 FTU/kg in NC grower and NC finisher diets respectively. Mean average daily gain (ADG), average daily feed intake (ADFI) and feed conversion ratio (FCR) were calculated for the feeding phases of 30–85 kg (grower), 85–125 kg (finisher) on trial and for overall period. During the grower phase, increasing phytase dose resulted in a linear increase in ADG. Phytase inclusion at 250, 500 and 1000 FTU/kg improved ADG by 3.5, 7.2 and 8.1% respectively compared to NC and by 0.8, 4.5 and 5.3% respectively compared to those fed the PC. Performance in the finisher phase, overall period and slaughter parameters were not different between dietary treatments. The data showed that it was beneficial to increase phytase dose up to 1000 FTU/kg in grower pigs up to 85 kg BW. In the finisher phase, in pigs with BW above 85 kg, 500 FTU/kg was sufficient to replace inorganic P and maintain performance and carcass characteristics comparable to pigs fed the PC.